2014
DOI: 10.11648/j.ajls.s.2014020602.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination among Bioagents, Compost and Soil Solarization on Management of Strawberry Fusarium Wilt

Abstract: Sterilized aqueous filtrate of the tested compost resulted in significant reduction to the linear growth of the tested fungus compared with control treatment. This reduction was gradually increased by increasing it‫׳‬s concentration. The combination among the bioagents B.subtilis and P.flurescens, compost and soil solarization resulted in significant reduction to strawberry Fusarium wilt with significant increase to the produced fruits and their total soluble solids (T.S.S.) , either each of them was used alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, the misuse of these inorganic substances has been an issue of public concern as they have destroyed the natural fertility of soil, killed beneficial soil organisms, reduced the natural resistance ability in crops, and also led to environmental pollution (Adhikary 2012;Keswani et al 2014;Bisen et al 2015). Several authors have also reported that certain pesticides, even at their recommended doses, are harmful to other beneficial species (Abida et al 2000;Nasreen et al 2003), and when sprayed, some part may remain in the agricultural land while some may enter the surrounding water, air, and soil (Malone et al 2004;Lefrancq et al 2013).Therefore, to overcome these problems, it is imperative to apply biological control like vermicompost and vermicompost tea as a safe and efficient alternative against such diseases, which have been considered important in the last few years for the control of many soil-borne phytopathogens (Abada and Ahmed 2014;Abada and Hassan 2017;Ragab Mona et al 2015;Devi and Das 2016). In organic farming, they play a very vital role in increasing the fertility of soil, nourishment of crops and fighting against diseases (Fig.…”
mentioning
confidence: 99%
“…However, the misuse of these inorganic substances has been an issue of public concern as they have destroyed the natural fertility of soil, killed beneficial soil organisms, reduced the natural resistance ability in crops, and also led to environmental pollution (Adhikary 2012;Keswani et al 2014;Bisen et al 2015). Several authors have also reported that certain pesticides, even at their recommended doses, are harmful to other beneficial species (Abida et al 2000;Nasreen et al 2003), and when sprayed, some part may remain in the agricultural land while some may enter the surrounding water, air, and soil (Malone et al 2004;Lefrancq et al 2013).Therefore, to overcome these problems, it is imperative to apply biological control like vermicompost and vermicompost tea as a safe and efficient alternative against such diseases, which have been considered important in the last few years for the control of many soil-borne phytopathogens (Abada and Ahmed 2014;Abada and Hassan 2017;Ragab Mona et al 2015;Devi and Das 2016). In organic farming, they play a very vital role in increasing the fertility of soil, nourishment of crops and fighting against diseases (Fig.…”
mentioning
confidence: 99%